River ecosystem resilience to extreme flood events. Issue 16 (24th July 2018) - Milner, Alexander M.; Picken, Jessica L.; Klaar, Megan J.; Robertson, Anne L.; Clitherow, Leonie R.; Eagle, Lawrence; Brown, Lee E.
Abstract: Floods have a major influence in structuring river ecosystems. Considering projected increases in high‐magnitude rainfall events with climate change, major flooding events are expected to increase in many regions of the world. However, there is uncertainty about the effect of different flooding regimes and the importance of flood timing in structuring riverine habitats and their associated biotic communities. In addition, our understanding of community response is hindered by a lack of long‐term datasets to evaluate river ecosystem resilience to flooding. Here we show that in a river ecosystem studied for 30 years, a major winter flood reset the invertebrate community to a community similar to one that existed 15 years earlier. The community had not recovered to the preflood state when recurrent summer flooding 9 years later reset the ecosystem back to an even earlier community. Total macroinvertebrate density was reduced in the winter flood by an order of magnitude more than the summer flood. Meiofaunal invertebrates were more resilient to the flooding than macroinvertebrates, possibly due to their smaller body size facilitating greater access to in‐stream refugia. Pacific pink salmon escapement was markedly affected by the winter flood when eggs were developing in redds, compared to summer flooding, which occurred before the majority of eggs were laid. Our findings inform a proposed conceptual model of three possible responses to flooding by the invertebrate community in terms of switching to different states and effects on resilience to future flooding events. In a changing climate, understanding these responses is important for river managers to mitigate the biological impacts of extreme flooding effects. Abstract : Extreme floods have a major influence in structuring river ecosystems, and with the projected increase in high‐magnitude rainfall events with climate change are expected to increase in many regions of the world in the future. Our study examines the effect of different flooding regimes and the importance of flood timing in structuring riverine habitat and their associated biotic communities. Our findings inform a conceptual model of three possible responses to flooding by the invertebrate communities in terms of switching to different states and effects on resilience to future flooding events.